ANALISA PENGGUNAAN ALAT BERAT PROYEK PEMBANGUNAN UNDERPASS SIMPANG DEWA RUCI DENPASAR, BALI - Andrea Saputra Antang Pratama, Fadjar Purnomo, Muhammad Fajar Subkhan (Prokons: Jurnal Teknik Sipil, 2014)
400 m long and 16 m wide Simpang Dewa Ruci underpass construction project is a new one in Bali. It is of drilled pile system which need heavy equipment for drilling.The purpose of this study is to find out the unit price of some heavy equipment, like drill pile, excavator back hoe, dump truck, wheel dozer, tandem vibratory roller, asphalt finisher, and pneumatic tire roller.The calculations result in unit price of job the drill with drill pile at IDR 93,921.79/m3, unit price of job entrenchment and soil moving with excavator back hoe at IDR 14,656.22/m3, unit price earth moving work with dump truck at IDR 38,324.82/m3, unit price leveling congeries with whell dozer at IDR 2,644.87/m3, unit price soil compaction and asphalt compaction with tandem vibratory roller at IDR 4,034.93/m3, unit price of the spreading asphalt with asphalt finisher at IDR 34,637.50/m3, and unit price asphalt compaction with pneumatic tire roller at IDR 13,478.42/m3.Keywords: capacity, heavy equipment, productivity, unit price, use